TWO FELLING TECHNIQUES AND FELLER POSTURES FOR INCREASING THE UTILIZATION OF GMELINA WOOD (A case study at two timber estates in East Kalimantan) - Sona Suhartana; Yuniawati Yuniawati (Indonesian Journal of Forestry Research, 2006)
Fellingis an early step in timber utilization process. Efficiencyand effectivity of felling technique, tool type and feller posture will affect the whole timber utilization efficiency. This study was carried out at two timber estates in East Kalimantan and intended to see the effect of two felling techniques and feller postures on felling productivity, fellingcost, as well as timber utilization efficiency.Primary  data collected in this research  included :  felling time, volume  of  felled timber, productivity, felling efficiency, stump height and felling cost. The data was analyzed using split-plot design with factorial pattern.The result showed that the implementation of lowest possible felling technique (LPFI) increased log production from 14.4  to 17.7%. The lowest stump height left was of  the one using LPFf  with particular bowed posture in PT. Sumalindo Lestari Jaya I (SLJ I) (4.82 cm).